Maandelijks informatieblad van de Gentse Studentenwerkgroep over Homofilie. (Gent : GeSWH, 1972)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : Pollepelstraat 42, 9000 Gent ; vanaf (1972) 3 : Hertstraat 1a, 9000 Gent
Nederlands
Periodiek